O professor de português e a literatura infantojuvenil: relações entre formação, hábitos de leitura e prática pedagógica - BATISTA, Janaína Bogéa Silva (2017)
The present research aims to investigate the relationships between formation, reading habits and pedagogical practice of the teaching of children's literature in the Portuguese Language classes of elementary education II of the São Luís municipal education network. This research privileged a qualitative methodological approach, in which were analyzed narratives of three teachers who work in the municipal school network. Through the testimonies collected in semi-structured interviews, it was sought to learn the experience of these teachers with the teaching of the Portuguese Language in the classroom environment, as well as the working conditions offered by the schools. For this purpose, questionnaires and interviews were used, as methodological tools, in order to obtain the data that provided the information regarding the participant’s subjects. In the analysis of these instruments, we sought to investigate the relationships between the training that these teachers had access to, the reading habits they developed, the literature conceptions of these subjects and their pedagogical practice. Authors such as Leffa (1999), Lajolo (2002), Soares (2004) and Kleiman (2009) contributed with reflections on Portuguese language teachers. The importance of reading and its conceptions was discussed. The teaching of literature in school and literary literacy were analyzed. The role of the teacher-mediator in the development of meaningful reading practices was highlighted. Likewise, the relevance of the adequate constitution of reading spaces for a meaningful work with reading was emphasized. The study highlights a contradiction between the training of teachers of Portuguese Language and the reality found in the classroom. It also reveals teachers with intense professional responsibility, interest in students' learning and their own updating. It identifies worried teachers, due to the lack of tools and resources that could help them in the classroom, overcrowded rooms associated with an extensive weekly workday, which has caused physical, mental and emotional exhaustion such as discouragement, discouragement with work and disenchantment with the classroom and with the teaching profession. The results of this research point out that Portuguese teachers need to become fluent literary readers so that this teaching practice can be appropriate to their audience, who are their students.